Exploring the risk factors for differences in the cumulative incidence of coeliac disease in two neighboring countries: the prospective DIABIMMUNE study. Issue 11 (November 2016) - ,; Knip, Mikael; Koski, Katriina; Koski, Matti; Härkönen, Taina; Siljander, Heli; Ryhänen, Samppa; Hämäläinen, Anu-Maaria; Ormisson, Anne; Peet, Aleksandr; Tillmann, Vallo; Ulich, Valentina; et al.
Abstract: Background: During the last several decades the prevalence of coeliac disease (CD) has increased worldwide. Aim: To compare the cumulative incidence of CD between Estonian and Finnish children and to identify the risk factors. Materials and methods: Children were recruited as part of the DIABIMMUNE Study. In the birth cohort (BC) 258 children from Estonia and 305 from Finland, and in the young children's cohort (YCC) 1363 and 1384 children were followed up, respectively. The diagnosis of CD was made in accordance with the ESPGHAN guidelines–the presence of IgA-tTG antibodies and small bowel villous atrophy. Results: During the study period 29 children developed CD. The cumulative incidence of CD was significantly higher in Finland (0.77% vs 0.27%; P = 0.01). No difference was seen between the children with CD and the controls in the duration of breastfeeding or the age at cereal introduction. The BC children with CD had had significantly more episodes of infections with fever by the age of 12 months compared to the controls (3.4 vs 1.4; P = 0.04). Conclusion: The 5-year cumulative incidence of childhood CD is significantly higher in Finland than in Estonia. Sequential infections early in life may increase the risk for developing CD.